2019
DOI: 10.1111/jfb.14137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GnRHa on plasma levels of Fsh and Lh in the female greater amberjack Seriola dumerili

Abstract: The effects of gonadotropin‐releasing hormone agonist (GnRHa) on plasma levels of follicle‐stimulating hormone (Fsh) and luteinising hormone (Lh) are reported for female greater amberjack Seriola dumerili with post‐vitellogenic ovarian oocytes. Five females were implanted with pellets containing GnRHa (600 μg kg−1 body weight), while five other females were injected with saline. All females implanted with GnRHa‐containing pellets ovulated 36–42 h post‐implantation. The GnRHa implants elevated Lh, but not Fsh p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Also, in quail, a model avian species, reports clearly state that the effects of GnRH on FSH are smaller than those on LH release 12,13 . This observation raises the same perplexing mystery indicated in teleosts in that GnRH has a small effect on FSH 1,[14][15][16] . Thus, it is postulated that an exclusive FSH-regulating hormone, FSH-RH, exists in vertebrates alongside GnRH.…”
mentioning
confidence: 77%
“…Also, in quail, a model avian species, reports clearly state that the effects of GnRH on FSH are smaller than those on LH release 12,13 . This observation raises the same perplexing mystery indicated in teleosts in that GnRH has a small effect on FSH 1,[14][15][16] . Thus, it is postulated that an exclusive FSH-regulating hormone, FSH-RH, exists in vertebrates alongside GnRH.…”
mentioning
confidence: 77%
“…This prevented oocytes from entering OM after the completion of vitellogenesis and finally resulted in oocyte atresia and spawning omission. The effects of the administration of gonadotropin-releasing hormone agonist (GnRHa) on OM and GtH plasma levels were examined in a greater amberjack broodstock of wild origin (Nyuji et al 2019). In fish whose ovaries contained oocyte at the end of vitellogenesis (oocyte diameter >600 lm), a significant increase in plasma concentrations of LH was observed 24 h after treatment, and all treated fish ovulated after 36-42 h, whereas only two out of five untreated control fish spawn spontaneously.…”
Section: Greater Amberjackmentioning
confidence: 99%
“…In the uterus, GnRH has been reported to act as a local regulator involved in the regulation of various uterine functions, including cell proliferation and apoptosis in the uterine endometrial cells, which are critical for menstrual health and successful implantation during pregnancy ( Imai et al., 1998 ; Meresman et al, 2003 ; Guo et al, 2018 ). The function of GnRH in the ovary involves interactions with other local and systemic hormones, specifically it is a modulator of the actions of LH and FSH ( Gong et al, 1995 ; Sonntag et al, 2005 ; Nyuji et al, 2019 ). In addition, it has been reported that GnRH in the uterus is intertwined with other hormonal pathways, such as those involving estrogen and progesterone ( Metallinou et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%